Capuchin: A Free-Climbing Robot. (12th April 2013) - Zhang, Ruixiang; Latombe, Jean-Claude
This paper describes an integrated quasi-autonomous four-limbed robot, named Capuchin, which is equipped with appropriate sensing, planning and control capabilities to "free-climb" vertical terrain. Unlike aid climbing that takes advantage of special tools and/or engineered terrain features, free climbing only relies on friction at the contacts between the climber and the rigid terrain. While moving, Capuchin adjusts its body posture (hence, the position of its centre of mass) and exerts appropriate forces at the contacts in order to remain in equilibrium. Vision is used to achieve precise contacts and force sensing to control contact forces. The robot's planner is based on a pre-existing two-stage "stance-before-motion" approach. Its controller applies a novel "lazy" force control strategy that performs force adjustments only when these are needed. Experiments demonstrate that Capuchin can reliably climb vertical terrain with irregular features.